FLEXIBLE ACRYLATE VERSUS CLASSIC-VIABLE THERAPEUTICAL SOLUTION - Dan Nicolae Bosînceanu; Dana Gabriela Bosînceanu; Maria Bolat; Raluca Baciu; Norina Forna (Romanian Society of Oral Rehabilitation, 2016)
Big variety of clinical cases is a very important element in choosing the peculiarities of development of creating the dentures. In the scope of these concerns enroll the present study, which aims to review, through clinical cases, the possibilities for treatment of edentulous by conventional methods but flexible acrylic material. The present study was performed in the Faculty of Dentistry Iasi, over four years, from 2008 to 2012, the group of patients is made up of those who were sent for prosthetic treatment declaring himself dissatisfied with conventional removable prosthetic dentures, represented be partial acrylic dentures or complete dentures. All patients in this study preferred flexible dentures to conventional ones due to traumatic experiences that have tried it with classical dentures and they restored their confidence that they can regain stomatognat system functionality.